2017
DOI: 10.21547/jss.322750
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics teachers’ use of source books other than textbooks: reasons, results and implications

Abstract: ÖzBu çalışmada, matematik öğretmenlerinin ders kitabı dışında kaynak kullanım durumlarının belirlenmesi ve öğretmenleri kaynak kitap kullanımına iten nedenlerin incelenmesi amaçlanmıştır. Bu amaç kapsamında şekillenen çalışma tarama modelinde betimsel bir araştırma olarak desenlenmiştir. Çalışmaya 100 ortaokul matematik öğretmeni katılmıştır. Katılımcılara açık uçlu sorulardan oluşan bir anket uygulanmıştır. Anketten elde edilen veriler içerik analizine tabi tutularak çözümlenmiştir. Yapılan analizler sonucund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Textbooks are compulsory at all levels of schooling for many years and teachers are required to follow these textbooks in classrooms since the centralized nature of the Turkish educational system is based on a curriculum. Thus, Turkish teachers actively use textbooks in their daily teaching practices and can often benefit from this curriculum resource to use them in their classrooms (Işık, 2008;Korkmaz et al, 2020;Özmantar et al, 2017;Uğurel et al, 2010;Ulusoy & Incikabi, 2020). Textbooks are designed in coordination with the curriculum, and the weekly distribution of subjects is predetermined.…”
Section: Digitalization In Education and Use Of Mathematics Textbooks In Turkish Educational Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Textbooks are compulsory at all levels of schooling for many years and teachers are required to follow these textbooks in classrooms since the centralized nature of the Turkish educational system is based on a curriculum. Thus, Turkish teachers actively use textbooks in their daily teaching practices and can often benefit from this curriculum resource to use them in their classrooms (Işık, 2008;Korkmaz et al, 2020;Özmantar et al, 2017;Uğurel et al, 2010;Ulusoy & Incikabi, 2020). Textbooks are designed in coordination with the curriculum, and the weekly distribution of subjects is predetermined.…”
Section: Digitalization In Education and Use Of Mathematics Textbooks In Turkish Educational Contextmentioning
confidence: 99%
“…The studies that investigated why the textbook is not used effectively in Turkey have considered different points. In studies that received views from teachers as to the use of mathematics textbooks, subjects such as the formal and visual features of the textbooks, the effect of central exams, the teaching methods and techniques adopted in content presentation, the number and quality of evaluating questions and activities were emphasized (Korkmaz et al, 2020;Özmantar et al, 2017;Ulusoy & İncikabı, 2020). For instance, Korkmaz et al (2020) found that the vast majority of teachers believe that textbooks are not suitable for central exams.…”
Section: Digitalization In Education and Use Of Mathematics Textbooks In Turkish Educational Contextmentioning
confidence: 99%
“…Aksi durum, bakanlık tarafından ilgili yönetmeliklerle sınırlandırılmıştır (MEB, 2012). Bununla birlikte İlköğretim Genel Müdürlüğü 2009 yılında "Ders Kitabı Dışında Kullanılacak Eğitim Araçları" ve Ortaöğretim Genel Müdürlüğü 2016 yılında "Yayın Aldırılması" konulu yazılarında bakanlığın belirlediği ders kitabı dışındaki kitaplarının aldırılmaması ve zorlayıcı tutum içinde olunmamasına yönelik ifadeler ve uyarılar içermektedir (Özmantar, Dapgın, Çırak-Kurt, İlgün, 2017). Ayrıca 2023 Eğitim Vizyonu Belgesinde "Yardımcı kaynak ihtiyacını büyük ölçüde ortadan kaldıracak düzenlemeler yapılacaktır" ifadesi ile bu duruma dikkat çekilmektedir (Sözer, 2019).…”
Section: Introductionunclassified
“…Ders kitabının kullanılıp kullanılmadığı, kullanılıyorsa nasıl kullanıldığı, öğrencinin öğrenme fırsatlarını etkileyebilmektedir. Bazı sınıflarda öğretmen kitabın istediği kısmını uyarlayarak kullanıp, geri kalan kısmını ihmal etmekte (Chavez-Lopez, 2003;Remillard, 2005), bazılarında ise ders kitaplarının yanı sıra yardımcı kaynaklar kullanılmaktadır (Özgeldi, 2012;Özmantar, Dapgın, Kurt & İlgün, 2017).…”
Section: Introductionunclassified
“…Whether textbooks are used or not and how they are used may influence students' learning opportunities. In addition, while some teachers adapt parts of textbooks and use those parts by completely ignoring the remaining parts (Chavez-Lopez, 2003;Remillard, 2005), some choose to use textbooks as supporting sources (Özgeldi, 2012;Özmantar, Dapgın, Kurt & İlgün, 2017). Due to various use of mathematics textbooks, this study adopts hypothetical enterprise for textbook analysis (Mesa, 2004;Stylianides, 2009).…”
Section: Introductionmentioning
confidence: 99%